The Use of Podcasts in Teaching Process Control - Palanki, Srinivas (Journal of Engineering Education Transformations, 2012)
There has been recent interest in Utilizing modern computer technology to enhance class room content delivery in engineering fields. Currently, most engineering education is delivered via traditional lectures to classes with a large number of students, which affords a very limited amount of exchange of ideas and students have difficult time grasping the relevance of what they should be learning. It has been shown that after roughly ten minutes of a typical lecture, about fifty percent of the class is inartentive. Many recent studies show that students learn better when they are engaged in an instructur-guided problems-solving environment. For the past three years, we have been using a novel approach to engineering education where podcasts or lecture videos are used in conjunction with problem-solving sessions to teach engineering. In this novel approach, the instructor records his lectures, ill advance, and these podcasts can be accessed asynchronously by students, before they come to class. In the class room, active- learning techniques are used for solving problems that are based on the podcast. This approach essentially switches the traditional role of lectures and home assignments in the sense that students view the lectures at home and do their home assignments in class. In this paper, we provide details on the technology utilized to make the podcasts using inexpensive desktop tools and student experience in using these tools in class. We f eel that the use of this paradigm is the future of engineering education and is particularly suited for a country like India, where the availability of well-designed podcasts can overcome the current shortage of well-qualified faculty members at the college-level.